Pengaruh Penerapan Model Discovery Learning Terhadap Kemampuan Penalaran Matematis Peserta Didik di Kelas VIII SMPN 8 Padang - MUHAMMAD FADLI (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematical reasoning ability is one of the abilities that must be possessed by every student in mathematics learning. But in reality the mathe|matical reasoning abi|lity of class VIII stu|dents of SMPN 8 Padang is n|ot op|timal. One of the factors that causes it to occur is learning that has not been fully able to facilitate students to develop mathematical reasoning abilities properly. Efforts can be made to improve students mathematical reasoning ability, one of which is to implement discovery learning models. T|he pur|pose of t|his stu|dy wa|s to deter|mine the differenses in mathe|matical reasoning abil|ities of stu|dents who use discovery lear|ning wit|h mat|hematical reasoning abilit|ies that use conventional lear|ning in the class VIII of SMPN 8 Padang. This type of research is a quasi-experimental research design with Static Group Design. The population in this study was class VIII SMPN 8 Padang with samples class VIII.E and VIII.F. The research instrument used was a tes of mathematical reasoning ability in the form of esaay quastion. Based on the analysis of the date from the final tes results obtained that at a significant level og 0,005 by performing the t-test obtained P-value = 0,048 because the P-v|alue < α th|en H0 is re|jected. This shows that students mathematical reasoning abilities with convensional learning in class VIII of SMPN 8 Padang. In this case, it can be concluded that the discovery learning model influences students mathematical reasoning abilities. Keywords – Discovery Learning Model, Mathematics Learning, The Ability of Mathematical Reasoning